Prechtl's diagnostics as a valuable research tool applied before implementation of NDT Bobath therapy - Monika Joanna Stecko; Agata Wawryków; Katarzyna Topczewska; Anna Stangret; Agnieszka Kordek; Katarzyna Weber-Nowakowska; Katarzyna Korabiusz (Kazimierz Wielki University, 2018)
Early Prechtl's diagnostics applied before implementation of NDT Bobath therapy was described in this article. Prechtl's diagnostics allows therapist to determine whether child development will be disturbed at psychomotor level and whether rehabilitation with the use of NDT Bobath method should be implemented. Quick implementation of the therapy allows to suppress improper motor patterns and develop proper distribution of muscle tone and change the repertoire of the movements in children. Key words: NDT-bobath, Prechtl's diagnostics, neurodevelopmental therapy.